The effect of solar irradiated vibrio cholerae on the immunochemistry of dendritic cells - Ssemakalu, Cano Cornelius (Vaal University of Technology, 2015)
Cholera is a waterborne disease caused by toxigenic strains of Vibrio cholerae. The spread of cholera in developing countries has largely been imputed to the unavailability of proper water treatment and sanitary infrastructure as well as poor hygiene. In order to prevent the contraction and spread of cholera the use of solar disinfection (SODIS) to treat water in waterborne endemic communities has been recommended by the World Health Organization (WHO). SODIS is a water sterilizing method that relies on natural sunlight to improve the microbiological quality of water. During SODIS the culturability of the water contaminating microorganisms is inactivated by the ultraviolet component of solar radiation. The success of SODIS treatment of water in alleviating the risks associated with the contraction of waterborne diseases such as cholera has been attributed to the effectiveness, with which the water is treated, simple application as well as low cost of materials required. Currently SODIS research has been dominated by studies geared towards understanding how the microbial inactivation occurs, enhancement of the disinfection process and health impact assessments. However, little to no research has been directed towards exploring the role played by the immune system following the consumption of the solar irradiated water pathogens such as V. cholerae. SODIS of microorganisms in water results in immunologically important microbial states and components that could induce an immune reaction or response. In view of the role of dendritic cells in shaping an immune response, the effect that solar irradiated V. cholerae in water has on the immunochemistry of the dendritic cells in vitro was investigated. Prior to the stimulation of the dendritic cells with the solar irradiated cultures of V. cholerae, the first objective required an evaluation on the impact that solar irradiation has on the production and secretion of the cholera toxin by V. cholerae in water. The results from this evaluation showed that solar ultraviolet radiation was incapable of inducing the secretion of the cholera toxin. Furthermore, there was extensive DNA degradation in the solar irradiated cultures of V. cholerae. The second objective was to investigate the ability for solar irradiated cultures of V. cholerae in water to induce the phenotypic maturation of immature dendritic cells in vitro. In order to achieve this objective, solar and non-solar irradiated, chemically/ heat inactivated and phosphate buffered saline (PBS) prepared cultures of V. cholerae as well as lipopolysaccharide (LPS) and cholera toxin-β (CTB) subunit were each used to stimulate immature dendritic cells. After 48 hours of stimulation the dendritic cells were assessed for the expression of CD54, CD80, CD83, CD86, MHC-I and MHC-II on their cell membrane. The results showed an increase in the expression of all the maturation phenotypic markers with CD54, CD86 and MHC-I being the most prominent ones on the surface of the dendritic cells stimulated with solar irradiated cultures of V. cholerae. The third objective was to assess the profile of the cytokines and chemokines secreted by the dendritic cells following their stimulation with solar and non-solar irradiated, chemically/heat inactivated and PBS prepared cultures of V. cholerae as well as LPS and CTB subunit. After 48 hours of dendritic cell stimulation the tissue culture media from each treatment was quantitatively and qualitatively analysed for the presence of interleukin (IL)-1α, IL-1β, IL-6, IL-7, IL-10, IL-12p40, IL-12p70, IL-15, IL-23, IL-27, macrophage inflammatory protein (MIP)-1α, MIP-1β, MIP-2, Regulated on Activation, Normal T cell Expressed and Secreted (RANTES) and tumor necrosis factor (TNF)-α. The analysis revealed that solar irradiated cultures of V. cholerae induced dendritic cells to secrete significant levels of pro-inflammatory cytokines in comparison to the unstimulated dendritic cells. Furthermore the profile of the cytokines and chemokines secreted by the dendritic cells in response to the solar irradiated cultures of V. cholerae in water was similar to that required to induce a T- helper (Th) Th2 immune response. The fourth objective was to assess the expression of the toll like receptor (tlr) genes by the dendritic cells following their stimulation with solar and non-solar irradiated, chemically/heat inactivated and PBS prepared cultures of V. cholerae as well as LPS and CTB subunit. After 48 hours of stimulation total RNA was extracted from the dendritic cells and subjected to real time quantitative polymerase chain reaction (RT qPCR) assay for tlr 1, 2, 3, 4, 5, 6, 9, 11, 12 and 13. The results showed no significant increase or decrease in the expression of most tlr genes in comparison to the unstimulated dendritic cells. This observation is synonyms with dendritic cell maturation. Taken together these findings show that solar irradiated cultures of V. cholerae were able to induce the maturation of immature dendritic cells in vitro. Furthermore dendritic cells stimulated with solar irradiated cultures of V. cholerae produced pro-inflammatory cytokines and chemokines. The results from this study suggests that the consumption of SODIS treated could provide immunological benefits.
D. Tech. (Department of Chemistry, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Vibrio cholerae; Cholera; Solar disinfection; SODIS; Dendritic cells; Immunity; Vaccine; Dissertations, Academic -- South Africa.; Cholera.; Vibrio cholerae.; Cholera -- Prevention.; Dendritic cells.